2004
DOI: 10.1523/jneurosci.4547-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline and Dopamine Efflux in the Prefrontal Cortex in Relation to Appetitive Classical Conditioning

Abstract: We trained rats to learn that an auditory stimulus predicted delivery of reward pellets in the Skinner box. After 2 d of training, we measured changes in efflux of noradrenaline (NA) and dopamine (DA) in the medial prefrontal cortex using microdialysis on the third day. Animals were subjected to a normal rewarded session and an extinction session, in which the auditory stimulus was presented alone. In the rewarded session, both NA and DA efflux were increased, but in extinction, only NA was activated. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 28 publications
3
51
0
Order By: Relevance
“…Third, DA elevations during the task, but not those of NA, were not significantly different from those observed in the anticipatory phase of the task, and this was the case for both groups of rats. These results are consistent with microdialysis studies showing that consumption of food or exposure to reward-predicting stimuli consistently increase DA release in the PFC (Bassareo and Di Chiara, 1997;Ahn and Phillips, 1999;Phillips et al, 2004) (but see Mingote et al, 2004). Furthermore, these results correlate with electrophysiological studies in monkeys, indicating that DA neurons fire in response to reward prediction (Schultz, 1998;Schultz and Dickinson, 2000).…”
Section: Na Da and Pfc Functionsupporting
confidence: 89%
See 1 more Smart Citation
“…Third, DA elevations during the task, but not those of NA, were not significantly different from those observed in the anticipatory phase of the task, and this was the case for both groups of rats. These results are consistent with microdialysis studies showing that consumption of food or exposure to reward-predicting stimuli consistently increase DA release in the PFC (Bassareo and Di Chiara, 1997;Ahn and Phillips, 1999;Phillips et al, 2004) (but see Mingote et al, 2004). Furthermore, these results correlate with electrophysiological studies in monkeys, indicating that DA neurons fire in response to reward prediction (Schultz, 1998;Schultz and Dickinson, 2000).…”
Section: Na Da and Pfc Functionsupporting
confidence: 89%
“…Handling (Dalley and Stanford, 1995;Kawahara et al, 1999;Feenstra et al, 2000) does not contribute to NA elevations because no change in NA efflux was observed when all of the groups of animals were moved from the home cage to the waiting cage or when untrained animals were placed from the maze back to their home cages. Elevations of PFC NA levels in response to stimuli that predict a reward have been shown previously (Mingote et al, 2004). It is known that food restriction or presentation of highly palatable food causes an increase in PFC NA efflux (Cenci et al, 1992;Taber and Fibiger, 1997;Feenstra, 2000;Feenstra et al, 2000).…”
Section: Discussionmentioning
confidence: 58%
“…Salient events or changing environmental contingencies, including extinction, have been shown to increase firing rates of noradrenergic neurons and NE efflux in forebrain structures (Foote et al, 1980;Sara and Segal, 1991;Mingote et al, 2004). In one study, locus coeruleus (the major source of forebrain NE) firing was increased following a shift to an extinction contingency, but this response rapidly decreased as extinction trials continued (Sara et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of noradrenergic neurons in the locus coeruleus facilitates retrieval of associative memories (Devauges and Sara, 1991;Sara and Devauges, 1988), and the presentation of cues associated with emotional stimuli activates these neurons (Sterpenich et al, 2006) and provokes norepinephrine release (Cassens et al, 1980;Feenstra et al, 2001;Mingote et al, 2004). Mice constitutively lacking dopamine b-hydroxylase (DBH), an essential enzyme in the synthesis of norepinephrine, are able to acquire contextual fear conditioning, but show a deficit in retrieval when tested on subsequent days (Murchison et al, 2004).…”
Section: Introductionmentioning
confidence: 99%